2010
DOI: 10.1007/s11858-010-0248-7
|View full text |Cite
|
Sign up to set email alerts
|

Modeling empowered by information and communication technologies

Abstract: In this article, we describe our work with mathematical modeling (MM) at different educational levels and discuss how the use of information and communication technologies (ICTs) empowered such work. Characteristics of two trends in research which have influenced our work are presented: one is a Brazilian perspective of MM, and the other is the use of ICTs in mathematics classrooms seen through the lens of the theoretical construct ''humans-with-media''. We introduce some key questions regarding the notion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
(13 reference statements)
0
3
0
3
Order By: Relevance
“…In our local context, 1 various (national or state) curriculum documents give some recommendations for working with MM at secondary school level and during mathematics teacher education. Although there are some local experiences at secondary schools working with open MM projects (Villarreal et al 2010;Villarreal and Esteley 2013), the engagement of teachers, pre-service teachers or students in active modelling is still scarce. The curriculum documents also emphasize the relationships between the real world and mathematics through modelling processes; however, most of the activities that are found in textbooks and classrooms are illustrative applications (Muller and Burkhardt 2007) to solve semi-real problems .…”
Section: Discussion and Final Considerationsmentioning
confidence: 99%
“…In our local context, 1 various (national or state) curriculum documents give some recommendations for working with MM at secondary school level and during mathematics teacher education. Although there are some local experiences at secondary schools working with open MM projects (Villarreal et al 2010;Villarreal and Esteley 2013), the engagement of teachers, pre-service teachers or students in active modelling is still scarce. The curriculum documents also emphasize the relationships between the real world and mathematics through modelling processes; however, most of the activities that are found in textbooks and classrooms are illustrative applications (Muller and Burkhardt 2007) to solve semi-real problems .…”
Section: Discussion and Final Considerationsmentioning
confidence: 99%
“…Tanto en el desarrollo de esta experiencia como de otras realizadas en el contexto de la enseñanza universitaria, fue posible observar el uso que los estudiantes hacían de tecnologías de diferente naturaleza para el desarrollo de proyectos de modelización. En Villarreal et al (2010) se describen proyectos de estudiantes de diferentes niveles del sistema educativo que muestran el papel de las tecnologías digitales en la producción de modelos matemáticos. En el estudio del rol de las tecnologías en los procesos educativos, el constructo humanoscon-medios (Borba & Villarreal, 2005) ha sido la perspectiva teórico-epistemológica desde la cual se analizó el uso de las tecnologías en la producción de conocimiento.…”
Section: Escenarios De Modelización Matemática Y Uso De Tecnologías D...unclassified
“…Studies in many countries have reported many barriers and issues to be addressed in order for teachers to implement computer software such as DGS in teaching (Crisan et al 2007; Kasten and Sinclair 2009;Monaghan 2004). Such use of the term empower is in accordance with how Villarreal et al (2010) use the term in their study of how the use of technology empowered students work with modelling. I use the term empower to describe how the teachers in different ways organised and helped their students to succeed with their work with the DGS in mathematics teaching.…”
Section: Background and Introductionmentioning
confidence: 97%